PROTECTION OF THE RIGHTS OF THE CHILD THE OBJECT OF ACTIVITY OF THE STATE AS: THEORETICAL AND PRACTICAL ASPECTS (Journal of actual problems of jurisprudence, 2019)
In this article is devoted to theoretical and practical questions baby’s law as to objections of functions of the states